The Educational Impact of Al-Azhar University in South Western Nigeria: A Case Study of Arabic-Islamic Schools in Yorubaland - Yunus Olatoke Abdus Salam; Saud Bin Mohammad (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2022)
Pursuing education in Arab countries generates a controversy among indigenous and home-made scholars in Nigeria. Some believe that it is enough to pursue religious education within the country, while some others uphold the standpoint that Muslim students should pursue their studies in Arab countries like Al-Azhar. Hence, there is a lot of confusion and controversy about the impact of Al-Azhar University in Nigeria. However, this study aims to investigate the impact of Al-Azhar University in Cairo, Arab Republic of Egypt on Arabic-Islamic schools in the Yorubaland, Nigeria. This is done through investigation of its curriculum, scholarship, and sending of Al-Azhar's delegates to teach in Arabic-Islamic schools in Yorubaland, Nigeria. It discusses Islamic religious affairs and the role played by the Nigerian Muslim scholars in general and in the South Western Nigeria in particular. Furthermore, it addresses the argument bothering on the need to pursue religious education within and outside the country. This study also examines the difference between Al-Azhar educational system and the Nigerian Arabic- Islamic educational system and investigates the need for continuation or otherwise of Al-Azhar’s venture in the Nigerian Arabic- Islamic Schools. This study is both historical and analytical in nature. It used data gathered via primary and secondary sources and utilizes both qualitative and quantitative methods. Findings from this study revealed the suitability of Al-Azhar educational system for Nigeria. It also showed the continuous need to pursue Al-Azhar education by Nigerians. The need to introduce some Western courses into Al-Azhar educational curriculum to facilitate easy fitting of the graduates into Nigerian educational system also emanated from this study. The study recommends the completion of secondary education in Nigeria by intending Nigerians seeking Al-Azhar education in order to facilitate their usefulness in the Nigerian western-oriented educational system upon their return.